Pengaruh Perputaran Kas dan Perputaran Piutang terhadap Profitabilitas PT Ultra Jaya Milk Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2012-2021 - Gunawan, Andri; Sardjana, Samuel Horas (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Data analysis techniques use descriptive data and correlation with a significant level of 5%. Based on the results of the partial study, cash turnover has a negative effect with a t-count value of -2.734 <t-table 2.026 and is significant for profitability with a value of 0.010 <0.05, while receivables turnover has a positive effect with a t-count value of 10.271> t table 2.026 and is significant for profitability. With a value of 0.000 <0.05. Meanwhile, simultaneously cash turnover and accounts receivable turnover show that F count is 69,438 > F table 3.25 with a significance level of 0.000 < a significance level of 0.05 so that it can be concluded that it has a positive and significant effect. The R square value of 0.794 which shows 79.4% ROA can be explained by independent variables, while the remaining 20.6 is explained outside of other variables.